PERAN MAHASISWA PLP (PENGENALAN LAPANGAN PERSEKOLAHAN) DALAM PEMBINAAN HAFALAN DAN KARAKTER SANTRI DI TAHFIZH PUTRI HIDAYATULLAH BOARDING SCHOOL BATAM - Afrizawati; Supiana, Sri; Nazila, Salwa; Tini, Ulfa; Marsanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of students in the Professional Field Practice Program (PLP) in fostering Qur’an memorization and strengthening the character of students at Tahfizh Putri Hidayatullah Boarding School Batam. The background of this research is based on the importance of student involvement as agents of change in supporting pesantren-based education, particularly in improving the quality of memorization and the development of Islamic character. The research method used is a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results show that PLP students play an active role as learning assistants, memorization mentors, and role models in character building through routine activities such as muroja’ah (revision), memorization submission, and the habituation of discipline and responsibility values. In addition, the presence of PLP students has a positive impact on increasing students’ learning motivation and the quality of learning interactions. Thus, the role of PLP students is considered effective in supporting the development of Qur’an memorization and students’ character. This study recommends strengthening collaborative programs between higher education institutions and Islamic boarding schools to improve the quality of education in a sustainable manner.